ACTR-15. PHASE 1 TRIAL OF A KETOGENIC DIET IN PATIENTS RECEIVING STANDARD-OF-CARE TREATMENT FOR RECENTLY DIAGNOSED GLIOBLASTOMA. (11th November 2019) - Gresham, Gillian; Amaral, Lauren; Lockshon, Laura; Levin, Dana; Rudnick, Jeremy; Provisor, Arlene; Shiao, Stephen; Bhowmick, Neil; Irwin, Scott; Freedland, Stephen; Hu, Jethro
Abstract: BACKGROUND: There is abundant interest in the potential therapeutic and supportive role of a ketogenic diet (KD) in patients with glioblastoma (GBM). The KD is a high fat/low carbohydrate metabolic therapy that modulates several of the bioenergetic and biosynthetic pathways that are dysregulated in GBM. To date, studies of the KD in cancer patients have been limited in scope. This study will provide preliminary evidence on the safety and feasibility of a 16-week ketogenic diet in patients with GBM. METHODS: This is an open-label single-arm feasibility trial being conducted at Cedars-Sinai Medical Center. We will recruit 20 recently diagnosed GBM patients who are receiving standard-of-care (SOC) treatment. Patients may enroll within 3 months of diagnosis, thus allowing patients who have already begun SOC chemoradiation the opportunity to participate. Excluded are patients with a KPS < 70, BMI < 22, or on high doses of steroids. Consenting patients will maintain a 16-week ketogenic diet (KD) supervised and monitored by study dietitians (RD). The primary outcome of safety will be assessed by monitoring weight, BMI, and adverse events. Secondary outcomes are: 1) Adherence to the KD, as assessed by BID blood glucose and ketone levels; 2) Time to progression and overall survival from date of KD initiation 3) Mean change in overall QOL, as measured using the QLQ30 and QLQ-BN20 questionnaires; and 4) Mean change in cognitive scores at 16 weeks from baseline. Exploratory outcomes include metabolic, inflammatory, and immune biomarkers; gut microbiota analysis; large oncosome analysis; and daily activity assessed with a wearable activity monitor. This novel trial incorporates multiple digital devices and mobile applications into the study design. Accrual is ongoing with 10 patients currently enrolled (NCT03451799).